ANALISIS KINERJA KEUANGAN DAERAH KABUPATEN TIMOR TENGAH UTARA - Godeliva Susan Sanbein; Kamilaus Konstance Oki; Paulina Rosna Dewi Redjo (UNPERBA, 2026)
North Central Timor (TTU) Regency still faces challenges in optimally managing regional potential and remains dependent on central government funding. To increase financial independence, it is crucial for the local government to manage resources efficiently and utilize local potential. The main problem is the low level of regional financial independence in North Central Timor (TTU) Regency. The method used in this study is a quantitative, involving the collection and analysis of numerical data to determine the financial performance of North Central Timor Regency. This study utilized secondary data from financial reports and related documents, collected through documentation and observation techniques. The analysis used financial ratios to measure fiscal independence and capacity. The results show that the level of regional financial independence for the 10-year period 2014-2023 was in the very low category, with an instructive relationship pattern. This indicates a high dependence on transfer revenues from the central government. Meanwhile, the regional fiscal capacity ratio was in the very low category throughout the period, with poor revenue potential and a relatively high dependence on central assistance.